2006
DOI: 10.1073/pnas.0509983103
|View full text |Cite
|
Sign up to set email alerts
|

The pupal specifier broad directs progressive morphogenesis in a direct-developing insect

Abstract: A key regulatory gene in metamorphosing (holometabolous) insect life histories is the transcription factor broad (br), which specifies pupal development. To determine the role of br in a directdeveloping (hemimetabolous) insect that lacks a pupal stage, we cloned br from the milkweed bug, Oncopeltus fasciatus (Of'br). We find that, unlike metamorphosing insects, in which br expression is restricted to the larval-pupal transition, Of'br mRNA is expressed during embryonic development and is maintained at each ny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
138
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(144 citation statements)
references
References 35 publications
5
138
1
Order By: Relevance
“…The br mutants exhibit abnormal regulation of many intermolt, early and late gene activities (Karim et al, 1993;Zhou and Riddiford, 2002). More recently, it has been demonstrated that br is expressed during each nymphal molt of the direct-developing insect Oncopeltus fasciatus (Erezyilmaz et al, 2006). Much less is known about the role of br in adult insects.…”
Section: Discussionmentioning
confidence: 99%
“…The br mutants exhibit abnormal regulation of many intermolt, early and late gene activities (Karim et al, 1993;Zhou and Riddiford, 2002). More recently, it has been demonstrated that br is expressed during each nymphal molt of the direct-developing insect Oncopeltus fasciatus (Erezyilmaz et al, 2006). Much less is known about the role of br in adult insects.…”
Section: Discussionmentioning
confidence: 99%
“…In more basal hemimetabolous, direct-developing insects data on the mechanisms of 20E action are practically nonexistent, with few exceptions (e.g., Erezyilmaz et al, 2006). The postembryonic development of hemimetabolous species shows significant differences with respect to holometabolous, especially because growth and maturation occur simultaneously throughout successively nymphal stages until the imaginal molt, without an intermediate pupal stage.…”
Section: Introductionmentioning
confidence: 99%
“…The A and B1 isoforms are expressed in complementary patterns, with one notable exception: the prothoracic gland, which exhibits expression of both isoforms (Talbot et al 1993). The other nuclear receptor, USP, is expressed ubiquitously and exhibits a DNA-binding motif that is required for repression, but dispensable for activation, of metamorphosis (Schubiger and Truman 2000;Ghbeish et al 2001;Erezyilmaz et al 2006). The mechanisms that lead to the activation of a specific receptor or, more often, a receptor isoform are still poorly known for ecdysone and most other steroid hormones across species.…”
mentioning
confidence: 99%